A Map of the British and French Settlements in North America : (part the first) containing Canada, Nova scotia, Newfoundland, New England, part of New York, with the Lakes, Six Nations, and all the countries westward in the same parallels so far as discover'd - Bowen, Thomas, d. 1790 (1755)
Relief shown pictorially. Prime meridian: London. Shows provinces, towns and cities, forts, Indian villages and tribal territory, missions, trails, some industries, and vegetation. Includes numerous historical and descriptive notes. Grayscale;